2010
DOI: 10.1074/jbc.m109.086371
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanisms of α-Amino-3-hydroxy-5-methylisoxazole-4-propionic Acid (AMPA) Receptor Binding to Glutamate and Kainate

Abstract: The ␣-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) subtype of ionotropic glutamate receptors mediates much of the fast excitatory neurotransmission in the central nervous system. The ability of these receptors to shape such responses appears to be due in part to dynamic processes induced by agonists in the ligand-binding domain. Previous studies employing fluorescence spectroscopy and whole cell recording suggest that agonist binding is followed by sequential transitions to one or more distinct co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 56 publications
5
45
0
Order By: Relevance
“…When full agonists are bound, the Asp655/Ser656 peptide bond flip results in the formation of two H-bonds between the carbonyl of Ser656 (lobe 2) and the amide of Gly453 (lobe 1) and between the carbonyl of Asp655and the amide of Tyr452 through a water molecule. The fully closed, H-bonding pattern exists on the time scale of approximately 100 ms (Fenwick and Oswald, 2010), which is the time scale of modal gating. The number and arrangement of subunits bound to agonist and in the H-bond locked state could determine the mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When full agonists are bound, the Asp655/Ser656 peptide bond flip results in the formation of two H-bonds between the carbonyl of Ser656 (lobe 2) and the amide of Gly453 (lobe 1) and between the carbonyl of Asp655and the amide of Tyr452 through a water molecule. The fully closed, H-bonding pattern exists on the time scale of approximately 100 ms (Fenwick and Oswald, 2010), which is the time scale of modal gating. The number and arrangement of subunits bound to agonist and in the H-bond locked state could determine the mode.…”
Section: Discussionmentioning
confidence: 99%
“…However, NMR studies and crystal structures of mutant GluA2 LBDs have suggested that the stability of the closed lobe may also contribute to agonist efficacy. Agonist binding consists of at least three steps: 1) binding to lobe 1, 2) closure of the lobes and contacts with lobe 2, and 3) interlobe contacts (including H-bonds) to stabilize the closed lobe form (Abele et al, 2000;Armstrong and Gouaux, 2000;Cheng et al, 2005;Robert et al, 2005;Weston et al, 2006;Zhang et al, 2008a;Fenwick and Oswald, 2010). Lobe closure is required for channel gating, but the degree of lobe closure that can trigger gating is not clear (i.e., does gating require a full closure?…”
Section: Introductionmentioning
confidence: 99%
“…After an initial control spectrum was taken in water, the protein was lyophilized and resuspended in D 2 O. A series of 1 H, 15 N HSQC/TROSY experiments (generally 12 sequential experiments) was performed at each of several temperatures, starting at 10°C up to 25°C (16).…”
Section: Methodsmentioning
confidence: 99%
“…The protein was then concentrated and stored in 20 mM sodium acetate, 25 mM sodium chloride, 1 mM sodium azide, and 10 mM glutamate at pH 5.5. The protein used for the glutamate (10 mM) and kainate experiments was prepared as described previously (16). AMPA (5 mM), kainate (10 mM), IW (2 mM), FW (2 mM), and NW (2 mM) were exchanged for glutamate by successive concentration and dilution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation